HYDROPONICS ALTERNATIVE USE AND OCCUPATION OF LAND IN DEGRADED AREAS: CROP CORN AND LETTUCE - Jerônimo, Carlos Enrique; Vasconcelos, Rykson (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2013)
http://dx.doi.org/10.5902/223611707164 There are hundreds of years Brazil has been undergoing a process of development, where fromthe time of its discovery the extraction and use of natural resources is being done in anuncontrolled way, degrading vast areas and the soil we inhabit and depend for our food supply.Especially the activity of agriculture emerges as a great responsibility in this scenario, however,closely followed numerous exploratory activities. Faced with this problem, science has beenstudying ways to recover or reuse areas that are or have undergone degradation processesphysical, chemical or biological. In this paper, a proposal is made to use hydroponic techniqueswith lettuce and corn, as an alternative form of land use, as well as the rational use of water,providing conditions for the development of agriculture in these areas. An evaluation mainly as areview of the use of this model as an alternative environmental compensation and reuse ofsewage or effluent from activities of oil exploration, installation of wind farms or mining activity.